Fortification of chocolate milk with omega-3, omega-6, and vitamins E and C by using liposomes - Marsanasco, Marina (2016)
The main goal of this work was to develop an additive to fortify a widely consumed product with vitamins. Additives were made of soy phosphatidylcholine (SPC)-based liposomes to encapsulate vitamin E (VE) and vitamin C (VC), and incorporated in chocolate milk to generate a functional food and posterior pasteurization. SPC contains essential fatty acids like omega-3 and omega-6 fatty acids. Stearic acid (SA) or calcium stearate (CaS) was incorporated as a liposome bilayer stabilizer. Characterization of liposomes involved size and surface charge, studied by light scattering and zeta potential, respectively. Liposome shape was analyzed by optical microscopy. Membrane packing was studied with merocyanine 540 and oxidative stability by the TBA and ORAC methods. The studies were made before and after pasteurization to study thermal stability. All formulations showed significant stability of the parameters analyzed, even after pasteurization, and a protective effect over VC, which is thermolabile. The release of vitamins was studied by dialysis. All additives were able to retain a high percentage of VE and VC. For food application, a sensory evaluation was performed in chocolate milk with liposomes. SPC:SA liposomes can be selected as food additives due to their acceptability and stability. Practical applications: Additives with a natural lipid SPC and vitamins E and C were developed to be incorporated in chocolate milk. They presented:. (1) A significant stability of all analyzed parameters before and after pasteurization:. – biophysical stability: size, structure, shape, molecular membrane packing and surface charge. – the oxidative stability: all had low peroxidation tendency. – thermal stability: all had a protective effect over thermolabile vitamin C after pasteurization. – temporal stability: all presented a high encapsulation of vitamins after 72 hours of dialysis. (2) Additives showed a Newtonian and pseudoplastic rheological behavior, both considered excellent for larger scale production. (3) Sensory evaluation of additives in commercial chocolate milk was performed by the overall acceptability with hedonic scale employing 40 potential consumers. SPC:SA formulation with vitamins was the most applicable. For all the above mentioned, the formulations, specially SPC:SA with vitamins E and C, are excellent candidates as additives to incorporated in chocolate milk. From liposomes to functional chocolate milk: Image: Liposomes: SPC, soy phosphatidylcholine; SA, stearic acid; CaS, calcium stearate. First graph: Vitamin C protection, pH > 5. Second graph: Sensory evaluation in chocolate milk, SPC:SA the best suited.